Average Error: 0 → 0
Time: 8.6s
Precision: 64
$b \lt m$
$\left(f - 1\right) \cdot \left(1 - \frac{b}{m}\right)$
$\left(f - 1\right) \cdot \left(1 - \frac{b}{m}\right)$
\left(f - 1\right) \cdot \left(1 - \frac{b}{m}\right)
\left(f - 1\right) \cdot \left(1 - \frac{b}{m}\right)
double f(double f, double b, double m) {
double r2493282 = f;
double r2493283 = 1.0;
double r2493284 = r2493282 - r2493283;
double r2493285 = b;
double r2493286 = m;
double r2493287 = r2493285 / r2493286;
double r2493288 = r2493283 - r2493287;
double r2493289 = r2493284 * r2493288;
return r2493289;
}


double f(double f, double b, double m) {
double r2493290 = f;
double r2493291 = 1.0;
double r2493292 = r2493290 - r2493291;
double r2493293 = b;
double r2493294 = m;
double r2493295 = r2493293 / r2493294;
double r2493296 = r2493291 - r2493295;
double r2493297 = r2493292 * r2493296;
return r2493297;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0

$\left(f - 1\right) \cdot \left(1 - \frac{b}{m}\right)$
2. Final simplification0

$\leadsto \left(f - 1\right) \cdot \left(1 - \frac{b}{m}\right)$

# Reproduce

herbie shell --seed 1
(FPCore (f b m)
:name "(f-1.0)*(1.0-b/m)"
:precision binary32
:pre (< b m)
(* (- f 1) (- 1 (/ b m))))